Comparing Strong and Weak Halogen Bonding in Solution: 13C NMR, UV/Vis, Crystallographic, and Computational Studies of an Intramolecular Model. Issue 38 (11th October 2017) - Widner, Danielle L.; Robinson, Emily R.; Perez, Alejandra B.; Vang, Herh G.; Thorson, Rachel A.; Driscoll, Zakarias L.; Giebel, Sierra M.; Berndt, Calvin W.; Bosch, Eric; Speetzen, Erin D.; Bowling, Nathan P.
Abstract : A series of arylene ethynylene compounds has been generated in order to study the differences between strong and weak intramolecular halogen bonding in solution. With strong intramolecular halogen bonding, the presence of electron‐withdrawing fluorine substituents near the halogen‐bond donor has a significant impact on the halogen bond and consequently on 13 C NMR chemical shifts. UV/Vis studies suggest increased conjugation of the arylene ethynylene backbone when strong halogen bonds are present. UV/Vis and NMR signatures of intramolecular halogen bonding are diminished significantly when electron‐withdrawing fluorine substituents are absent, however. This change in behavior is further illustrated by differences in crystallization tendencies with the presence or absence of electron‐withdrawing substituents. Calculations using the M06‐2X functional provide some insight into the energies associated with both strong and weak intramolecular halogen bonding. Abstract : Electron‐withdrawing fluorine groups are commonly installed near halogen‐bond donors to increase Lewis acidity. Are these substituents necessary, however, when the halogen‐bond donor and acceptor are connected by an aryldiyne linker?